2019
DOI: 10.1093/jbcr/irz083
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Intoxication and the Postburn Gastrointestinal Hormonal Response

Abstract: Gastrointestinal hormones are essential in postburn metabolism. Since near 50% of burn victims test positive for blood alcohol levels at hospital admission and have inferior outcomes compared to nonintoxicated burn patients; we hypothesized that the gastrointestinal hormone secretion is compromised in intoxicated burn victims. To test our theory, we quantified gastrointestinal hormones serum levels in a combine ethanol intoxication and burn injury mouse model. Thus, mice received a daily dose of ethanol for 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Thus, the hyperglycemia we found in animals of the first and second experimental groups is explained in the first case by the well-known effect of CAI, which can cause disorders of carbohydrate metabolism, manifesting in both hyper- (more often) and in hypoglycemia [ 68 , 69 ], and in the second case by a response to stressful effects. At the same time, a significant decrease in the levels of this metabolite in the blood plasma of rats of the third group was caused by a disruption of the adaptation process.…”
Section: Discussionmentioning
confidence: 84%
“…Thus, the hyperglycemia we found in animals of the first and second experimental groups is explained in the first case by the well-known effect of CAI, which can cause disorders of carbohydrate metabolism, manifesting in both hyper- (more often) and in hypoglycemia [ 68 , 69 ], and in the second case by a response to stressful effects. At the same time, a significant decrease in the levels of this metabolite in the blood plasma of rats of the third group was caused by a disruption of the adaptation process.…”
Section: Discussionmentioning
confidence: 84%
“…Although both burn injury and chronic alcohol consumption promote hypermetabolism, there are few studies which explore the impact of combined alcohol intoxication and burn injury on metabolic outcomes. One recent study revealed significant alterations in metabolism after combined insult, including hyperglycemia and changes in serum insulin, glucagon and gastrointestinal hormones in alcohol and burn mice compared to sham or burn alone 35 . In our study, almost all KEGG pathways significantly associated with upregulated genes in IECs after alcohol and burn injury were metabolic in nature (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although both burn injury and chronic alcohol consumption promote hypermetabolism, there are few studies which explore the impact of combined alcohol intoxication and burn injury on metabolic outcomes. One recent study revealed signi cant alterations in metabolism after combined insult, including hyperglycemia and changes in serum insulin, glucagon and gastrointestinal hormones in alcohol and burn mice compared to sham or burn alone 35 . In our study, almost all KEGG pathways signi cantly associated with upregulated genes in IECs after alcohol and burn injury were metabolic in nature (Fig.…”
Section: Discussionmentioning
confidence: 99%